Causative Organisms and Risk Factors In Bacterial Meningitis in Al-Elwia Childhood Hospital - Baghdad - Abdul Hameed, Ban (AL-Kindy College Medical Journal, 2011)
Background: Childhood meningitis is a majorcause of morbidity and mortality, Hemophilusinfluenza b (Hib) is the most common cause inmany countries, especially below 5 years andbefore the development of conjugated Hib vaccine,it is followed by Streptococcus Pneumonia, andthen N. meningitides, in addition to othermicroorganisms.Objective: To identify the causative organismsof bacterial meningitis and to identify the factorspredisposing significantly to the incidence ofbacterial meningitis.Method: This cross sectional , study was done inAl-Elwia Pediatric Hospital during the period 1stof January 2007 to 30th of June 2007.Eighty fourpatients with presumptive diagnosis of meningitiswere included in this study, from the age of 2months -12 years, History about some risk factorswere taken in details. Analysis of cerebrospinalFluid (CSF) with Gram stains & cultures weredone in all cases.Results: The number of cases of meningitis was50 (20 proved meningitis & 30 partially treatedmeningitis), while 34 patients are found to have nomeningitis.Streptococcus pneumoniae was identified in45%, Hemophilus Influenza b in 20%, whileNisseria meningitides 5%, other organisms includeEscherichia coli, Staphylococcus aureus,Klebsiella, & salmonella.Many factors affecting the occurrence ofbacterial meningitis & these include: age, sex,residence, body weight and home overcrowding.Conclusions: Streptococcus pneumoniae wasfound to be the predominant microorganismcausing bacterial meningitis in children aged 2months-12 years, followed by Hemophilusinfluenza b, while N. meningitides were one of therare bacteria which had been identified. E. coli wasfound to be the major cause in cases of ventriculoperitoneal(VP) shunt meningitis.